Penerapan Media Pembelajaran Berbasis Scramble Untuk Meningkatkan Keterampilan Membaca Siswa pada Mata Pelajaran Bahasa Indonesia di SDN 014 Pulau Binjai - Mutiara Khairunnisa; Radhiyatul Fithri; Wismanto Wismanto (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2024)
Reading is very important to be learned by everyone, especially those who are in education. Therefore, teachers try to improve students' reading skills, one of which is by implementing scramble learning media. This study aims to improve students' reading skills through scramble learning media. This research method uses a qualitative method with the type of Classroom Action Research (PTK), which consists of 2 cycles and each cycle has 2 meetings. The data collection techniques are through observation, interviews, and documentation. The results of the study obtained from the application of scramble-based learning media to teachers in cycle I from 52% to 64% and for cycle II from 75% to 88%. The application of scramble-based learning media to students in cycle I from 39% to 50%, and for cycle II from 61% to 66%. Meanwhile, for students' reading skills before the implementation of this scramble learning media, the percentage value was 37%, after the implementation of the scramble media, students' skills increased with cycle I from 37% to 53%, and for cycle II from 72% to 79%. Thus, through the implementation of this scramble-based learning media, it can improve students' reading skills at SDN 014 Pulau Binjai.